A concept analysis of transcultural in nursing practices - Rahayu, Kusila Devia; Rosa, Ronnell D. Dela; Vallesteros, Liwayway T. (The Journal of Palembang Nursing Studies, 2024)
Background: Differences in interpreting the term ‘transcultural’ in nursing practice need to be addressed. Inappropriate terminology in the nursing practice environment may impact the quality of health care. Objective: The aim of this research is to identify the meaning of transcultural in concepts and theories and its relationship to the practice of the nursing profession. Methods: This paper was designed for Walker and Avant concept analysis. Reputable articles from indexing databases were used for review. “Transcultural” AND “Transcultural Nursing Practice” were the two key concepts used in the literature search. The inclusion criteria for articles to be retrieved were determined by the authors with high rigor. Then, an organizing framework was formulated using Walker and Avant’s conceptual analysis method.  Results: Antecedents, attributes, and consequences are inferred from the keywords or sentences in each article. The antecedents in this study include immigrants, acculturation, immigration, emigration, cultural diversity, cultural competence, interpersonal caring, transcultural nursing, and cross-cultural comparisons. The attributes in this study encompass cultural exchange, overcoming obstacles, research development, changes to standards and operating procedures. The consequences of the transcultural concept for nursing practice include its impact on organizations, patients/clients, and nurses. Conclusions: We suggest that healthcare professional thoroughly comprehend transcultural concepts in nursing practice in order to effectively apply transcultural approaches in nursing practice. This is one way to improve the quality of healthcare services.